Pengaruh Kepemimpinan, Remunerasi Dan Mutasi Terhadap Kinerja Pegawai Kantor Imigrasi Kelas II Non TPI Agam - Zulkifli, Zulkifli; Heliyani, Heliyani (CV. ITTC INDONESIA, 2021)
Nowadays, every government organizational are supposed to increase their job performance, which is used to give excellent service to the customer/society. In order to achieve goal is needed qualified human resources. The research was conduct at the Agam Immigration Office. The purpose of this research was to determine the effects of leadership, mutation, and remuneration on employee performance, by distributing questionnaires for 42 civil servants and conduct interviews and observations. Then the data is processed used quantitative analysis methods by using SEM (structural equation models) analysis technique based on Smart PLS variance.The result showed that leadership has positive effect on job performance, the remuneration has positive effects to job performance and mutation has positive effect to job performance.